2006
DOI: 10.1269/jrr.0575
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Response of Blood Lymphocytes of Inhabitants Residing in High Background Radiation Areas of Ramsar- Micronuclei, Apoptosis and Comet Assays

Abstract: The hot springs in certain areas of Ramsar contain (226)Ra and (222)Rn. The effects of natural radiation on the inhabitants of these areas and the inhabitant's radiosensitivity or adaptive responses were studied. One group of volunteers from areas with high natural background radiation and another group from areas with normal background radiation were chosen as the case and control group respectively. The frequency of micronuclei, apoptosis, and DNA damage in peripheral blood mononuclear cells were measured fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Many studies show adaptive responses on a molecular, cellular, organ and organism level following an initial primed dose and consequently higher resistance to mid-lethal challenge doses and also to non-radiogenic toxins [21][22][23]34,35,47,64 . Resistance has also been seen at specific times post initial irradiation during which the induced resistance also may operate against nonradiogenic, i.e., spontaneous cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies show adaptive responses on a molecular, cellular, organ and organism level following an initial primed dose and consequently higher resistance to mid-lethal challenge doses and also to non-radiogenic toxins [21][22][23]34,35,47,64 . Resistance has also been seen at specific times post initial irradiation during which the induced resistance also may operate against nonradiogenic, i.e., spontaneous cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological studies have shown evidence of hormetic effects 47 . Human lymphocytes from individuals living in high background radiation areas irradiated with a 1.5 Gy challenge dose showed significantly lower incidence of DNA damage than the control lymphocytes 47 . These results may indicate an adaptive response induced by high background radiation levels.…”
Section: Epidemiologymentioning
confidence: 99%
“…There is evidence that DNA repair underlies the AR induced by low radiation doses in human and plant cells (Lambin et al, 1994;Patra et al, 2003) by increasing the amount and rate of DNA repair (Joiner et al, 1996;Joiner et al, 1999). For example, when peripheral blood mononuclear cells from residents of Ramsar (a high natural background radiation area) were irradiated with a challenging dose of gamma rays, Mohammadi et al (2006) detected lower levels of micronuclei, higher numbers of apoptotic cells and enhanced DNA repair. It has been proposed that these effects could be related to the induction of an AR.…”
Section: Sakamoto-hojomentioning
confidence: 99%
“…The mean effective dose resulting from 226 Ra due to consumption of vegetables from this area is reported to be 12 times greater than the average effective dose resulting from this radionuclide due to foods and drinking water in normal area (Ghiassi-Nejad et al, 2003). Some of studies which have conducted by various molecular methods on HBRAs of Ramsar have shown that the spontaneous level of DNA damage in the lymphocytes of the inhabitants in these regions was significantly higher than control groups Mohammadi et al, 2006).…”
Section: Introductionmentioning
confidence: 84%